answersLogoWhite

0


Best Answer

7p + 2 = 5p + 8

7p - 5p = 8 - 2

2p = 6

p = 3

User Avatar

Wiki User

โˆ™ 2011-03-03 15:40:44
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.8
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
1775 Reviews

Add your answer:

Earn +20 pts
Q: What is 7p plus 2 equals 5p plus 8?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

What is 7p plus 5q equals -3 find q when p equals 1?

7p+5q=-3, p=1 7Xp+5q=-3 7+5q=-3 5p=-10 p=-2


4p plus 9 plus -7p plus 2 equals?

4p+9-7p+2 -3p+11 p = 11/3


Simplify this expression 4p plus 9 plus minus 7p plus 2 equals?

4p + 9 - 7p + 2 4p - 7p + 9 + 2 p(4 - 7) + 9 + 2 -3p + 11


Simplify this expression 4p plus 9 plus 7p plus 2 equals?

11p+11


What is the answer to this question 7p plus 2q equals 46 and 5p plus 3q equals 36?

7p + 2q = 46 . . . . (A) 5p + 3q = 36 . . . . (B) 3*(A): 21p + 6q = 138 2*(B): 10p + 6q = 72 Subtracting gives 11p = 66 so that p = 6 Substitute for p in (A): 7*6 + 2q = 46 or 42 + 2q = 46 which gives 2q = 4 so that q = 2 Solution: (p, q) = (6,2)


Simplify 4p plus 9 plus -7p plus 2?

4p + 9 + (-7p) + 2 = 4p - 7p + 9 + 2 = -3p + 11


3p plus 4p plus 10 equals 5p plus 2 what is the value of p?

3p + 4p +10 = 5p + 2 Subtracting 5p from both sides: 3p + 4p - 5p + 10 = 5p + 2 - 5p ie 2p + 10 = 2 Subtract 10 from both sides: 2p + 10 - 10 = 2 - 10 ie 2p = -8 Divide both sides by 2: p = -4


What is the solution set for 2p2-5p plus 2 equals 0?

2p2-5p+2 = 0 (2p-1)(p-2) = 0 p = 1/2 and p = 2


15 equals 5 plus 9p-4p?

15 = 5 +( 9p - 4p) 15 = 5 + 5p 15 - 5= 5 -5 +5p 10 = 5p there for p = 10/5 = 2


What is the answer to 7p plus 2?

7p+2 is an algebraic expression. Since it is neither an equation nor an equality, it cannot have a solution or answer.


How do you simplify this expression 4p plus 9 plus 7p plus 2?

Collect like terms together: 4p + 9 + 7p + 2 = (4p + 7p) + (9 + 2) = (4 + 7)p + 11 = 11p + 11 = 11(p + 1)


If 7p plus 5q equals -3 find q when p equals 1?

Look at it this way: If p = 1, then 7p = 7. What plus 7 equals -3? Adding 7 to -10 would equal -3, so all we have to figure out is what times 5 would equal -10. 5 times -2 would equal -10 so q equals -2.

People also asked